Ultra-processed food consumption by Brazilian adolescents in cafeterias and school meals - Noll, Priscilla Rayanne e Silva (Sci Rep, 2019)
This cross-sectional study utilized the National School Health Survey 2015 database to assess the association between school cafeterias; the meals offered by the Brazilian School Food Program (PNAE); and the consumption of industrialized/ultra-processed salty foods, sweets, and soft drinks among Brazilian adolescents. A sample of 102,072 adolescents, aged 11–19 years, who were enrolled in the 9th grade completed the survey. The evaluated outcome was the consumption of industrialized/ultra-processed salty foods, sweets, and soft drinks. A Poisson regression model-based multivariate analysis was performed. The effect measure was the prevalence ratio (PR) with its respective 95% confidence intervals (CIs). The results indicated that Brazilian adolescents who attended schools without meals offered through the PNAE had a higher probability of regularly (≥5 times/week) consuming ultra-processed salty foods [PR = 1.06, CI = 1.01–1.11] and soft drinks [PR = 1.08, CI = 1.03–1.14] compared to those who attended schools that offered PNAE meals. Moreover, the presence of a school cafeteria was associated with a higher probability to consume industrialized/ultra-processed salty foods [PR = 1.05, CI = 1.02–1.08], sweets [PR = 1.09, CI = 1.07–1.11], and soft drinks [PR = 1.10, CI = 1.07–1.13]. School meals appear to be associated with the consumption of ultra-processed foods by Brazilian adolescents, indicating areas for health promotion programs.